Two jasmonic acid carboxyl methyltransferases in Gossypium hirsutum involved in MeJA biosynthesis may contribute to plant defense - Teng, Dong; Jing, Weixia; Lv, Beibei; Huang, Xinzheng; Zhao, Danyang; Kou, Junfeng; Liu, Xiaohe; Dhiloo, Khalid Hussain; Zhang, Yongjun (Frontiers in Plant Science, 2023)
Jasmonic acid (JA) and methyl jasmonate (MeJA), the crucial plant hormones, can induce the emission of plant volatiles and regulate the behavioral responses of insect pests or their natural enemies. In this study, two jasmonic acid carboxyl methyltransferases (JMTs), GhJMT1 and GhJMT2, involved in MeJA biosynthesis in Gossypium. hirsutum were identified and further functionally confirmed. In vitro, recombinant GhJMT1 and GhJMT2 were both responsible for the conversion of JA to MeJA. Quantitative real-time PCR (qPCR) measurement indicated that GhJMT1 and GhJMT2 were obviously up-regulated in leaves and stems of G. hirsutum after being treated with MeJA. In gas chromatography-mass spectrometry (GC-MS) analysis, MeJA treatment significantly induced plant volatiles emission such as (E)-β-ocimene, (Z)-3-hexenyl acetate, linalool and (3E)-4,8-dimethyl-1,3,7-nonatriene (DMNT), which play vital roles in direct and indirect plant defenses. Moreover, antennae of parasitoid wasps Microplitis mediator showed electrophysiological responses to MeJA, β-ocimene, (Z)-3-hexenyl acetate and linalool at a dose dependent manner, while our previous research revealed that DMNT excites electrophysiological responses and behavioral tendencies. These findings provide a better understanding of MeJA biosynthesis and defense regulation in upland cotton, which lay a foundation to JA and MeJA employment in agricultural pest control.